Introduction to eristics for pedagogues - Logos. Formal correctness of the argument - Agata Marciniak (Studia z Teorii Wychowania)
Interpersonal communication should not be reduced to a simple transfer of information. Modern theories of communication underline the fact that the complete process of communication realizes broadly understood social influence with e.g. all its emotional aspects. From this perspective a knowledge about eristics seems to be especially useful for every pedagogue and teacher for which a professional activity requires effective communication with students – let us add, an eristics neutrally understood as an organon. This article is the first part of the series on eristics. The whole series of texts is dedicated to those teachers and pedagogues who want to develop their communication skills. This first part of the series focuses on the essence and methods of using logos tactic, with particular emphasis on techniques that are based on the formal structure of the argument.